MARKETING STRATEGY OF THE KAIN TENUN MICRO, SMALL, AND MEDIUM ENTERPRISES IN WISATA KAMPUNG TENUN, SAMARINDA CITY - Febriyani, Sandra; Ningsih, Novita Surya (Progress In Social Development, 2025)
The Micro, Small, and Medium Enterprises “Cahaya Samarinda” is one of the pioneers in the weaving industry development in Samarinda. The Cahaya Samarinda only did their marketing through words of mouth. The purpose of this study was to determine and identify the marketing strategies used by Cahaya Samarinda in Tenun Tourism Village. This study used the 4P marketing concept by Philip Kotler. The four elements, which were product, price, place, and promotion, were used as an analytical framework to identify how Cahaya Samarinda as an MSME managed its tenun fabric products, determined selling prices, carried out promotional activities, and chose distribution channels. This research is descriptive qualitative, with informants selected by using purposive sampling. Data analysis includes data reduction, data presentation, and drawing conclusions. The results of the study showed that Cahaya Samarinda had advantages in product quality at affordable prices. However, this MSME still had room to widen the market range through the use of social media and participation in exhibitions. Although the location of the store was not strategic, high-quality products and good service became the main attractions for customers.